The Day of the Week Effect on the - Ioffe, Stanislav (My University, 2015)
This research examines the day-of-the-week effect on the JSE Securities Exchange for the period from 1995 to 2007. This effect was documented in the 1970s and 1980s. The first democratic election in 1994 left the international isolation of South Africa behind, and the financial markets opened up to foreign investors, bringing the possibility that political and economic changes could impact on market behaviour and anomalies. Time series of the JSE daily closing prices comprised JSE/Actuaries All Share Index (Code: CI01) for the period 1st of January, 1995 until 21st of June 2002 and FTSE/JSE All Share Index (Code: J203) for the period 24th of June, 2002 until 31st of December, 2007. The presence of the day of the week pattern was tested by conducting daily return mean variance examinations and formal statistical analysis of tradingtime hypothesis. The latter was implemented by means of regression analysis. The study shows that the day-of-the-week effect is no longer present on the JSE Securities Exchange. The absence of the systematic day-of-the-week pattern suggests that investors may have improved risk pricing due to higher efficiency of the stock market. It is not advisable for investors to use any kind of active trading strategy based on exploiting the previously reported day-of-the-week anomaly
MBA - WBS
Keywords: Day of the week effect; Johannesburg Securities Exchange